Management of Tracheo‐esophageal Fistulae with Montgomery T‐Tube. (2nd September 2014) - Tran, Christopher M.; Fink, Daniel S.; Kunduk, Melda; McWhorter, Andrew J.
Abstract : Objectives: (1) Describe a minimally‐invasive technique for management of trachea‐esophageal fistulae. (2) Analyze outcomes of management of trachea‐esophageal fistulae with t‐tube placement. Methods: A retrospective case series with chart review was conducted at an academic practice in a regional referral center. Two patients with tracheo‐esophageal fistulae who either were not candidates for open surgical repair or refused open surgical repair were successfully managed with a Montgomery T‐tube to stent the fistula. Outcome measures included resumption of oral diet, need for further procedures, and fistula size. Results: Both patients had t‐tubes that were sized to stent the fistula and maintain an airway without esophageal stent or tracheostomy. There were no cases of migration or enlargement of fistula. No patients required revision procedures. Fistulae were successfully controlled in all patients, with full resumption of oral intake and maintenance of voice. No patients had closure of fistula. Conclusions: Montgomery T‐tube stenting is a safe and minimally invasive way to manage trachea‐esophageal fistulae in patients who are not candidates for open surgical repair. This technique minimizes soilage of the airway with maintenance of voice that is often difficult in management with cuffed tracheotomy tubes. Neither migration nor enlargement of fistula was noted.